Fig. 6 in Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica - Matsubayashi, Makoto; Tsuchida, Sayaka; Kobayashi, Atsushi; Shibahara, Tomoyuki; Nakamura, Hiroshi; Murata, Koichi; Ushida, Kazunari (Zenodo, 2018)
Fig. 6. Histopathologic sections of ceca which were obtained from dead chicks infected with Eimeria spp. Arrowhead indicates macrogametocytes with a prominent wall-forming body (A), and arrows indicate zygotes or early oocysts, which are surrounded by an oocyst wall (A and B). Pathological lesions could not be observed because of severe degradation after death. Scale bars indicate 20 μm. Published as part of Matsubayashi, Makoto, Tsuchida, Sayaka, Kobayashi, Atsushi, Shibahara, Tomoyuki, Nakamura, Hiroshi, Murata, Koichi & Ushida, Kazunari, 2018, Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica, pp. 243-250 in International Journal for Parasitology: Parasites and Wildlife 7 (3) on page 249, DOI:10.1016/j.ijppaw.2018.06.005, http://zenodo.org/record/13135846